The Analysis of the Influence of Organizational Citizenship Behavior on Productivity with Turnover Intention and Performance as Mediator - Priliana, Lina; Hidayat, Rahmat (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2025)
This study aims to analyze the effect of Organizational Citizenship Behavior (OCB) on employee productivity at PT Emsonic, with Turnover Intention and performance as mediating variables. The respondents in this research are employees in the production department of PT Emsonic, totaling 221 respondents. Data were analyzed using SEM (Structural Equation Modeling) with LISREL 8.80. The results indicate that (1) OCB does not have a positive and significant effect on productivity, (2) OCB has a positive and significant effect on performance, (3) Turnover Intention negatively and significantly affects both productivity and performance, (4) Performance positively and significantly influences productivity, (5) OCB negatively and significantly affects Turnover Intention, (6) Turnover Intention mediates the relationship between OCB and productivity, and (7) Performance mediates the relationship between OCB and productivity.